The Effect Of Public Accountability And Public Transparency On Employee Performance In The Regional Secretariat People's Welfare Bureau Of West Sumatra Province - Pathila, Dora; Adnan, M. Fachri (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2023)
This study aims to examine the effect of public accountability and public transparency on the performance of employees of the Bureau of People's Welfare Regional Secretariat of West Sumatra Province. The research method is a quantitative descriptive method using a total sampling technique, in which the questionnaires are distributed directly to all employees of the People's Welfare Service. The data analysis technique used in this research is data description, classical assumption testing and hypothesis testing. The results of this study indicate that public accountability and public transparency partially and simultaneously have a positive and significant effect on the performance of employees at the Bureau of People's Welfare Regional Secretariat of West Sumatra Province.